2021
DOI: 10.3390/ijerph18147423
|View full text |Cite|
|
Sign up to set email alerts
|

Work-Related Satisfaction among Clinicians Working at Inpatient Treatment Facilities for Substance Use Disorder: The Role of Recovery Orientation

Abstract: Several psychosocial factors have been suggested as facilitators of change among inpatients treated for substance use disorder (SUD). Research suggests that staff members are also influenced by the practice in which they are involved, and by contextual psychosocial factors at their treatment facilities. This cross-sectional questionnaire survey study was conducted to investigate the role of recovery-orientated interventions in describing work-related satisfaction among clinicians at inpatient SUD treatment fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 71 publications
(121 reference statements)
0
2
0
Order By: Relevance
“…24 This concept is highly compatible with the community mental health services that support patientsʼ community lives. Studies have shown that knowledge of recovery reduces psychiatric staff prejudice, 25 being recovery-oriented increases the sense of achievement and job satisfaction of psychiatric staff, 26,27 and psychiatric staffʼs experience in recovery-oriented practices enhances their self-efficacy. 28 Therefore, it was predicted that the psychiatric staffʼs reduction of prejudice toward patients, recovery orientation, and increase in job satisfaction and self-efficacy would be interrelated and that these factors would positively affect the number of visits.…”
Section: Psychological Factors Of the Respondentsmentioning
confidence: 99%
“…24 This concept is highly compatible with the community mental health services that support patientsʼ community lives. Studies have shown that knowledge of recovery reduces psychiatric staff prejudice, 25 being recovery-oriented increases the sense of achievement and job satisfaction of psychiatric staff, 26,27 and psychiatric staffʼs experience in recovery-oriented practices enhances their self-efficacy. 28 Therefore, it was predicted that the psychiatric staffʼs reduction of prejudice toward patients, recovery orientation, and increase in job satisfaction and self-efficacy would be interrelated and that these factors would positively affect the number of visits.…”
Section: Psychological Factors Of the Respondentsmentioning
confidence: 99%
“…In the published article [ 1 ], there was an error regarding the affiliations for Trond Nordfjærn . In addition to the affiliation Department of Psychology, Norwegian University of Science and Technology (NTNU), 7491 Trondheim, Norway should be Department of Research and Development, Clinic of Substance Use and Addiction Medicine, St. Olavs University Hospital, 7006 Trondheim, Norway .…”
Section: Additional Affiliation(s)mentioning
confidence: 99%